Fireworks - Burgess, Matthew (Clarion Books, an imprint of HarperCollins Publishers, 2025)
Part poem, part portable fireworks display with a vertical gatefold, this POB picture book from the award-winning team of Matthew Burgess and Cátia Chien highlights the simple delights of a steamy July day in the city as two siblings eagerly await a spectacular fireworks display. POP! As a hot day sizzles into evening, everyone on stoops and sidewalks looks skyward on this special summer night -- the Fourth of July! Words and art blossom into flowers of fire across the sky, making this a perfect read for firework enthusiasts in cities and suburbs everywhere. POP! POP!